Does overground robotic gait training improve non-motor outcomes in patients with chronic stroke? Findings from a pilot study. (November 2020) - De Luca, Rosaria; Maresca, Giuseppa; Balletta, Tina; Cannavò, Antonino; Leonardi, Simona; Latella, Desiree; Maggio, Maria Grazia; Portaro, Simona; Naro, Antonino; Calabrò, Rocco Salvatore
Highlights: Patients with stroke present long term non motor symptoms, including constipation. Robotics has proven effective in improving functional recovery in patients with stroke. Ekso may be a useful tool in improving post-stroke non motor symptoms. Abstract: Stroke is the leading cause of disability among the elderly in the industrialized world. No more than 40% of stroke survivors walk independently, and only after receiving appropriate rehabilitation treatment; many stroke patients have also non-motor symptoms. The aim of this pilot study is to evaluate the effects of Ekso-training on non-motor outcomes, including gastrointestinal function and psychological well-being, in post stroke patients. We enrolled 30 post-stroke subjects, which were randomized into two groups in order of recruitment: 15 patients were trained with the overground exoskeleton Ekso-GT (experimental group, EG), whereas 15 patients were submitted to a standard gait training (control group, CG). Both the groups underwent the same amount of physiotherapy. At the end of the training, only in the EG we observed a significant improvement in constipation, mood, and coping strategies, with regard to social support, as well as in the perception of quality of life (as per SF-12). According to these preliminary data, overground robotic gait training can be considered a valuable tool in improving non-motor symptoms, including constipation and behavioral disorders in patients with chronic stroke.